MEMBANGUN KEMAMPUAN BERPIKIR KRITIS MELALUI PERCOBAAN RANGKAIAN LISTRIK MENGGUNAKAN PHET SIMULATION DENGAN PENDEKATAN INKLUSIF - Dendodi, Dendodi (Universitas Tanjungpura, 2025)
This study aims to develop students' thinking skills through the theory and application of electrical circuit experiments using PhET Simulation with an inclusive approach. The scope of the research involves twelfth-grade students from SMAS Indonesia Muda Sungai Raya who participated in physics lessons, particularly on the topic of electrical circuits. The research method employed is an experimental design using a pre-experimental (pretest-posttest) approach. The sample consists of 18 twelfth-grade students with diverse academic abilities and learning needs, including students with special needs. Based on data analysis using the Wilcoxon test, a value of 0.000 0.05 (sig Î±) was obtained. The N-Gain score was 0.6259, which falls within the range of 0.3 - 0.7, categorizing it as moderate. Additionally, the N-Gain percentage reached 62.5944%, indicating that the increase in students' abilities was within the range of 56-75%, considered fairly effective in proving that the use of theory and application in electrical circuit experiments with PhET Simulation had a significant impact on students' critical thinking skills. The average critical thinking skills of the students increased significantly after being given the intervention through theory and application of electrical circuit experiments with PhET Simulation. The conclusion of this study is that PhET Simulation is an effective tool in supporting the learning of electrical circuits and can foster students' critical thinking skills, especially when applied with an inclusive approach.